Correlation of Individual Characteristics and Work Stress among Go-Jek Drivers during the Pandemic - Richa Rifana Aida; Indriati Paskarini (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Go-Jek Drivers have experienced a change in condition due to the declining number of Go-Jek users during the pandemic. One of the impacts is work stress. This research aims to determine the relationship between individual characteristics and the work stress of Go-Jek drivers during the pandemic. Methods: This research used a cross-sectional design and the total population sampling technique where the population was all members of the Go-Jek motorbike driver community in Semolowaru Surabaya, totaling 65 people. Age, marital status, total dependents, and working period were the independent variables. Work stress was the dependent variable. The retrieval of data was done using a questionnaire based on the Minister of Manpower Regulation No.5 of 2018 to measure work stress. To determine the relationship between age and working period with work stress, this study used the Pearson test. The relationship between total dependents and work stress was determined using Fisher's exact test. The relationship between marital status and work stress used the contingency coefficient method. Results: In total, 39 drivers (60%) experienced moderate work stress and 26 drivers (40%) experienced heavy work stress. The relationship of age with work stress was very weak (0.040), the relationship between marital status and work stress was very weak (0.013), the relationship between total dependents and work stress was very weak (0.131), and the relationship between working period and work stress was weak (0.234). Conclusion: The relationships between age, marital status, and the total dependents with work stress are very weak, and working period and work stress also have a weak relationship.